(3dZR aj daX bGfhfs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3CeG HYO GdMeO hGdUdGI ajbhd eMeO GdeTJgQ HHgGA GdOjf GdYGedi Efg bO jYQV ef eWGdYI GdYdhe GdOjfjI hcdGd jQOY ef eRGhdI GdCYeGd GdCNQhjg s
(3BNQgG (B:s
(3hdfbJUQ Ydi gPG GdbOQ ef GdEWfGH ai PcQ ChUGa Pdc GdcJGH hGdYGbd jcajI GdETGQI hGdLGgd dGjfJaY HCda YHGOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B23s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HMhGTjgG JYdjbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs